Criminal liability provisions arising from traffic accidents within the framework of the profession of teaching driving - Rahman, Dilshad Abdul; Al-Mazouri, Yousif (Journal of Legal and Political Studies, 2024)
The nature of the work of driving education offices always takes into account the presence of a strong possibility of traffic accidents occurring, and these accidents can become a source of attacks on the values and interests protected by the penal legislator, especially since the person who wants to learn to drive a car needs a period of practical training through education offices. In particular, these offices need human capabilities, technical and logistical supplies and conditions, and any shortage or shortcoming in these human capabilities or technical and logistical requirements and conditions may cause traffic accidents that result in an attack on the values and interests subject to criminal protection. Hence, the issue of criminal liability for such incidents can be raised.
Keywords: the work of driving education offices; Criminal liability; traffic accidents